Laissez-Faire vs. Government Intervention: Implications of Regulation Preventing Nonauthorized Remanufacturing - Esenduran, Gökçe; Jin, Minyue; Zhou, Yu (Manufacturing and Service Operations Management, 2025)
Problem definition: In this paper, we compare laissez-faire and mandatory authorization policy regimes for third-party remanufacturing. Under a laissez-faire policy, an independent remanufacturer (IR) chooses whether to get the original equipment manufacturer (OEM) authorization. Under a mandatory authorization policy, the IR is required to get OEM authorization and to pay the OEM a fee for every item remanufactured. Motivated by China’s regulatory journey that first mandated authorized remanufacturing and then moved to a laissez-faire policy, our goal is to understand which policy is better from the perspectives of different stakeholders. Methodology/results: We use a game-theoretic approach and consider a supply chain consisting of a supplier, an OEM, and an IR under the two policy regimes. Conventional wisdom suggests that the IR would be better off under the laissez-faire policy, but the OEM and the supplier would be better off under the mandatory authorization policy. However, we show that this conventional wisdom may not hold. For products with a low remanufacturing cost, all firms benefit from the mandatory authorization policy, whereas for products with a moderately high remanufacturing cost, all firms are better off under the laissez-faire policy. Further, mandatory authorization may outperform the laissez-faire policy in both economic and environmental dimensions. Managerial implications: Our findings reveal that seemingly advantageous policy regimes may backfire for firms. Therefore, before supporting such policies, the firms need to assess the strategic reactions of other firms and the potential impacts on their profits. Furthermore, a mandatory authorization policy can be beneficial in fostering the development of the remanufacturing sector for products with low remanufacturing costs. Nevertheless, it may also lead to an increase in the total environmental impact. Funding: The work of M. Jin was supported by the National Natural Science Foundation of China [Grants 72071020 and 72471038]. The work of Y. Zhou was supported by the National Natural Science Foundation of China [Grants 71971033 and 72371040] and the Fundamental Research Funds for the Central Universities [Grant 2024CDJSKPT14]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/msom.2023.0128 .